ДОСЛІДЖЕННЯ ВПЛИВУ ВЕУ НА ВЕЛИЧИНУ СТРУМУ МІЖФАЗНОГО КОРОТКОГО ЗАМИКАННЯ ЧЕРЕЗ ЕКРАНИ КАБЕЛІВ МЕРЕЖІ ВЕС НАПРУГОЮ 10-35 кВ - Буйний, Р.О.; Діхтярук, І.В.; Красножон, А.В.; Квицинський, А.О. (Інститут електродинаміки Національної академії наук України, 2020)
Shown the principle for calculation of double-fault ground current on a branch of electric power network with two sources (one of the sources can be a wind electric plant while the other source can be a power line). In cable shields with double ground fault the currents will be from the two sources. Thus, all the sources should be taken into account for calculation the ground fault currents and selection of the cable’s shield cross-section. Analyzed the influence of power network specifications on double-fault ground current and shown that such an influence is small, except the correspondence between subtransient currents of triple faults on both sides of the cable power line. In case of grounding the cable shields from one side of the power line, the full current of the double fault will flow through the single-core cable. So, it will require using cables with substantially larger cross-sections. It is found that the dissipation resistance of electric ground of cable shields does not significantly affect the double-fault ground current. References 5, figures 4.